iARBook: An Immersive Augmented Reality system for education - Bazzaza, Mhd Wael; Al Delail, Buti; Zemerly, M. Jamal; Ng, Jason W. P. (2014 IEEE International Conference on Teaching, Assessment and Learning for Engineering (TALE), 2014)
The advancement in technology nowadays has improved learning methods that are beginning to override the traditional methods. Augmented Reality (AR) is one such technology that has seen many applications in education. This paper describes how an Immersive Augmented Reality (iAR) application in conjunction with a book, can act as a new smart learning method by engaging as many of the user's senses and human functions as possible. In addition, a survey was conducted on students and educators who have tested the application. The purpose of the survey is to study the effectiveness of the application in enhancing the user's learning experience and help to devise plans to improve the system.